2010
DOI: 10.1007/dcr.0b013e3181bcd3cc
|View full text |Cite
|
Sign up to set email alerts
|

Downstaging After Chemoradiotherapy for Locally Advanced Rectal Cancer: Is There More (Tumor) Than Meets the Eye? Downstaging after chemoradiotherapy for locally advanced rectal cancer: is there more (tumor) than meets the eye?

Abstract: Patients with a mural pathologic complete response have a low rate of positive lymph nodes. These findings may have implications for the management strategies of these patients, including the use of local resection or a watch-and-wait policy. When the response to chemoradiotherapy is not complete, radical surgery should remain the treatment based on high rates of lymph node involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(35 citation statements)
references
References 49 publications
2
32
1
Order By: Relevance
“…Emerging data suggest that lymph nodes might well respond in a similar manner as the primary tumour. In patients with a complete pathological response, node positivity is no greater than 5% [4,5,11,13]. While absolute certainty of lymph node status can only be achieved by radical excision, this data shows inter-institutional consistency and reproducibility and supports a role for primary radiation therapy in management of loco-regional lymph node disease.…”
Section: Discussionmentioning
confidence: 63%
“…Emerging data suggest that lymph nodes might well respond in a similar manner as the primary tumour. In patients with a complete pathological response, node positivity is no greater than 5% [4,5,11,13]. While absolute certainty of lymph node status can only be achieved by radical excision, this data shows inter-institutional consistency and reproducibility and supports a role for primary radiation therapy in management of loco-regional lymph node disease.…”
Section: Discussionmentioning
confidence: 63%
“…They concluded that the local recurrence rate would be too high and recommended against TEM for patients with ypT2 rectal cancers after CRT. 13 Considering their previous prediction, the authors should not be surprised by their current results.…”
mentioning
confidence: 75%
“…13 In a previous publication from the same group, Doctor Perez analyzed the results of 88 patients with ypT2 treated with TME selected from a larger group of 401 patients treated with CRT. 14 Similar to the present study, 112 patients with a cCR to CRT were not operated on and were excluded for the analysis.…”
mentioning
confidence: 99%
“…However, direct examination of the primary tumor may not be sufficient to determine a complete clinical response (cCR), and surface biopsies of the residual scar may not be conclusive and in some cases even misleading [43,44]. Furthermore, 2-9% of patients with an absence of residual primary tumor are found to have positive lymph nodes at pathological examination [32, [45][46][47][48] and,…”
Section: Rectal Surgery: Complications Functional Outcome and Quality mentioning
confidence: 99%